THE DEVELOPMENT OF PRINCIPLES OF THE PUBLIC CONSTRUCTION PROCESS - Krampuža, Ilga (Administrative and Criminal Justice, 2018)
The aim of the article is to research the process of development of principles of the public construction process. The author shows the stages of formation and consolidation of the principles of the public construction process, as well as reflects the main tendencies in the future.As regards the construction process, there are many interests which come into conflict and which can be contradictory among themselves. First of all, there are the neighbours’ interests which are mainly related to the issues of private law, and, secondly, the public or general interests which are mainly related to the right to a favourable environment. The objective of the principles of the public construction process is to ensure protection of these interests. During the first years of existence of the Republic of Latvia, special attention was paid to the construction legal regulation. The principles of construction during this period are closely related to the desire to create a system that provides construction according to a predetermined plan and order and serves the restoration of the national economy after the historical shocks. Following the restoration of the independence of the Republic of Latvia, the principles of construction are to be derived from the conditions provided by regulatory enactments and recognised as an instrument that provides for the transition to the implementation of the public construction process that is appropriate to the Western legal scope. Thanks to the new Construction Law, the construction principles have been “embedded” in the law as legal norms, which allow solving problems of the persons involved into construction process, as well as the issues of neighbourhood and environmental protection according to the modern needs.